Public perceptions of threat in Britain: security in an age of austerity - Stevens, Daniel (UK Data Service, 2013)
No longer are British interests at home and abroad considered to be under threat from one particular state, but rather from a complex web of threats. Yet, despite a tripling of the security budget since 2001, little is known about public attitudes towards security threats, what sorts of issues ordinary people find threatening, whether they agree with, or are aware of, governments' attempts to make them feel more "secure", and whether these attempts have any impact. Stevens and Vaughan-Williams' project is to investigate: how members of the public understand the concepts of "threat" and "security" what they consider to be the most pressing threats to their security how and whether perceived threats to security influence other political attitudes whether their views coincide with notions of threat and how to respond to and mitigate them in the government's National Security Strategy. The research is based on 20 mini-groups of three respondents from the main regions of Britain, as well as a large-scale survey of 2000 respondents. The results will be compared and contrasted with elite representations of threat, as found in, inter alia, the National Security Strategies.